The Role of Clay Minerals in the Petrophysical Properties of Carbonate Rocks from the Cotinguiba Formation (Sergipe-Alagoas Basin, Brazil) - da Luz, Clarissa Oliveira; da Silva Jr., Gerson Cardoso; dos Santos Ribeiro, Mariléa Gomes (Anuário do Instituto de Geociências, 2023)
The Cotinguiba Formation, of Cretaceous age, located in the Sergipe-Alagoas Basin, Brazilian Northeastern coast, comprises carbonate breccias and carbonate shales interlayered with fine to coarse clastic sediments (mudstones, marls), deposited in the maximum sea level episode during the Cenomanian-Coniacian transgressive event. Core sections were selected from the formation materials, from which 20 plugs were obtained, representing the main carbonate horizons present in Cotinguiba Formation. The selected samples were analyzed with petrophysical and physical methods (air porosimetry, mercury injection, and acoustic wave velocity) and mineralogical methods (optical microscopic analysis, x-ray diffraction (XRD) and scanning electron microscopy (SEM)). Results showed that the clay minerals’ content in the carbonates varies from 2% to 20%, with illites/micas and interstratified illite/smectite as the most abundant clay minerals, containing also traces of chlorite and kaolinite, and presence of palygorskite varying from trace to 8%. According to the percentages of calcite, dolomite, and siliciclastic + clay minerals obtained in the XRD analysis, the carbonates were lithologically identified as limestone, impure limestone, dolomitic limestone, impure dolomitic limestone, impure calcitic dolostone, and impure dolostone. The rocks have a good porosity, varying from 6% to 20% in the carbonates, predominantly related to microporosity. Clay minerals’ content influenced the grain density and acoustic properties, albeit not having the same role with porosity and permeability. SEM images, though, show that they have an important role in microporosity. Grain density variation related to phyllosilicate content was observed more significantly in impure limestones with a clay content higher than 8%, and a more pronounced decrease was observed in samples with palygorskite. Microporosity is the main factor for reducing Vp and Vs velocities in those carbonates, with values not exceeding 5341 m/s for Vp and 3026 m/s for Vs but, when clay content is higher than 4%, the Vp and Vs wave velocities do not exceed 4100 m/s and 2480 m/s, respectively. Therefore, the research allowed evaluating the influence of mineralogical and textural properties in the petrophysical properties of Cotinguiba Formation.